2012
DOI: 10.1039/c1em10601e
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of two commercial chemiluminescence NOxanalysers according to European Standard EN 14211

Abstract: According to Directive 2008/50/EC, all equipment used for NO(x) fixed measurements must comply with the reference method or equivalent by 11 June 2013. Up to that date, non-type-approved equipment can continue to be used in air monitoring networks and will probably also be used in air pollution studies even after that date. In this context, it is advisable to know how these "old" measuring instruments respond to the requirements of European Standard EN 14211: 2005: Ambient Air Quality--Standard method for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Flow 2.0 can measure, every minute, the air quality indices (AQI) and the air concentration levels of different pollutants: nitrogen dioxide (NO 2 ) and volatile organic compounds (VOCs) in ppb v / v , as well as particulate matter equal to or less than 10 and 2.5 microns (PM 10 and PM 2.5 , respectively) in . Although the manufacturer guarantees the precision and reproducibility of the sensor measurements [ 35 ], the portable gauges were validated in the laboratory in a dynamic reference chamber which generated controlled atmospheres [ 36 , 37 , 38 , 39 ]. The measurements provided by the Flow 2.0 were controlled by measurements taken with the continuous analysers Thermo model 42i for NO–NO 2 –NO x , 48i for CO, 49i for O 3 , and 450i for SO 2 –H 2 S, and Syntech Spectras GC955 gas chromatograph for other chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…Flow 2.0 can measure, every minute, the air quality indices (AQI) and the air concentration levels of different pollutants: nitrogen dioxide (NO 2 ) and volatile organic compounds (VOCs) in ppb v / v , as well as particulate matter equal to or less than 10 and 2.5 microns (PM 10 and PM 2.5 , respectively) in . Although the manufacturer guarantees the precision and reproducibility of the sensor measurements [ 35 ], the portable gauges were validated in the laboratory in a dynamic reference chamber which generated controlled atmospheres [ 36 , 37 , 38 , 39 ]. The measurements provided by the Flow 2.0 were controlled by measurements taken with the continuous analysers Thermo model 42i for NO–NO 2 –NO x , 48i for CO, 49i for O 3 , and 450i for SO 2 –H 2 S, and Syntech Spectras GC955 gas chromatograph for other chemicals.…”
Section: Methodsmentioning
confidence: 99%
“…Further details on these changes are discussed by Doval Miñarro and González Ferradás. 8 3 Results and discussion…”
Section: Methodsmentioning
confidence: 99%
“…Estimated parameters of eqn(8) together with their standard errors and the residual sum of squares (RSS)…”
mentioning
confidence: 99%
“…FID were proved to be affected as well (LeBouf et al, 2013); however, these tests were performed at ppm levels. Among the reference measurement techniques to measure air pollutants, chemiluminescence with ozone to measure NO and NO2 is also humidity-dependent (Gerboles et al, 2003;Hayden, 2003;Miñarro and Ferradás, 2012;Steinbacher et al, 2007); and also UV photometry to measure ozone (Wilson and Birks, 2006). Recently, Bluhme et al (Bluhme et al, 2016) have shown that measurements of SH2 by UV fluorescence are also affected.…”
Section: Influence Of Humidity On Benzene Measurementsmentioning
confidence: 99%